Cutaneous Primary Cryptococcosis in an Immunocompetent Patient: Case Report - Aranha,Nicole S (2021)
ABSTRACT Cryptococcosis is a systemic infection caused by Cryptococcus neoformans, an encapsulated opportunistic yeast. It primarily causes significant infections in immunocompromised individuals and the symptoms vary according to the integrity of the immune system. Cutaneous cryptococcosis affects about 20% of patients with disseminated cryptococcosis, but primary cutaneous cryptococcosis (PCC) without systemic infection is rare. A 76-year-old male patient with chronic obstructive pulmonary disease, hypertension and dyslipidemia, presented with a violaceus inflammatory skin plaque with blisters that progressed despite intravenous ceftriaxone for 7 days. Histopathology of an incisional biopsy was compatible with the diagnosis of cutaneous cryptococcosis. There was a complete response to fluconazole 300 mg/day for 3 months. No systemic disease was detected and there was no evidence of immunosuppression. The importance of including cutaneous cryptococcosis in the differential diagnosis of skin lesions in patients without immunosuppression or the use of immunosuppressive therapy is emphasized. The cutaneous manifestations of the infection can be the first indication for a disseminated disease, therefore, its early recognition is essential to obtain a good prognosis.